The Wnt signaling pathway in cancer - Duchartre, Yann; Kim, Yong-Mi; Kahn, Michael (Critical reviews in oncology/hematology, 2016)
The Wnt signaling pathway is critically involved in both the development and homeostasis of tissues via regulation of their endogenous stem cells. Aberrant Wnt signaling has been described as a key player in the initiation of and/or maintenance and development of many cancers, via affecting the behavior of Cancer Stem Cells (CSCs). CSCs are considered by most to be responsible for establishment of the tumor and also for disease relapse, as they possess inherent drug-resistance properties. The development of new therapeutic compounds targeting the Wnt signaling pathway promises new hope to eliminate CSCs and achieve cancer eradication. However, a major challenge resides in developing a strategy efficient enough to target the dysregulated Wnt pathway in CSCs, while being safe enough to not damage the normal somatic stem cell population required for tissue homeostasis and repair. Here we review recent therapeutic approaches to target the Wnt pathway and their clinical applications.